Analysis of the linear geometric values of the maxillary sinuses in adults, and their gender differences - M.B. Cherkes (Danylo Halytsky Lviv National Medical University, 2020)
Aim. To formulate general data about the linear geometric parameters of the maxillary sinuses using cone-beam computed tomography, and to determine possible gender influence on these indicators.